PERAN EKONOMI KREATIF DALAM PEMBERDAYAAN INDUSTRI KERAJINAN BAMBU - NING MALIHAH; SITI ACHIRIA (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
This study aims to see how the role of the creative economy in an effort to empower the bamboo handicraft industry in the village of Tulungagung. Businesses that have been running so far have major problems related to capital and marketing. So that there needs to be empowerment that contains training to overcome the problem. Lack of capital can be overcome by providing training and the formation of bamboo woven / cooperative BMTs for artisans. Meanwhile, marketing problems, which in this case also involve the creation of goods made/output. So there is a need for training in innovation to increase the value of bamboo crafts. The results of this study, namely the creative economy in Tulungagung Village has been going well. The existence of a creative economy, as a form of creative and innovative ideas for the community and its economic benefits.